The Effect of Content Quality, Interactivity, and Social Media Posting Consistency on Brand Awareness of the Nutrition Clinic at Pertamina Cilacap Hospital - Destiana Pertiwi; Zulfikar Yusya Mubarak; Nuni Wulansari (Jurnal Ekonomika dan Manajemen, 2026)
This study aims to examine the effect of content quality, interactivity, and posting consistency on brand awareness of the Nutrition Clinic at Pertamina Cilacap Hospital through Instagram and TikTok social media platforms.  Data were obtained from 140 respondents selected through non-probability sampling with a purposive sampling technique, consisting of social media users domiciled in Cilacap who were familiar with the Nutrition Clinic’s Instagram and TikTok accounts. Data were collected using a Likert scale questionnaire and analyzed using SPSS version 26 through descriptive analysis, instrument testing, classical assumptions, and hypothesis testing. The results indicate that content quality, interactivity, and posting consistency have a positive and significant effect on brand awareness, both partially and simultaneously. Among the three variables, posting consistency shows the most dominant influence. These findings suggest that informative and engaging content, active interaction with audiences, and consistent content publication play an important role in enhancing public awareness of Nutrition Clinic services. This study is expected to contribute to the development of digital marketing studies in the healthcare sector and to provide practical insights for hospitals in designing more effective social media promotion strategies.